2015
DOI: 10.2527/jas.2015-9172
|View full text |Cite
|
Sign up to set email alerts
|

Drought effect on weaning weight and efficiency relative to cow size in semiarid rangeland1

Abstract: Cow size has been suggested to be an important consideration for selecting cattle to match their production environment. Over the last several decades, the trend in genetic selection for maximum growth has led to gradual increases in beef cow size. An unrelated trend during this same period in the western United States has been an increase in temperature, drought frequency, and drought severity. Due to the potential influence of the increasing cow size trend on nutritional maintenance costs and production, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 52 publications
4
34
0
1
Order By: Relevance
“…But other measures of productivity (pregnancy rates and net returns) were comparable with LGHT cow productivity, even though measures of weaning efficiency (kg of calf BW weaned per 100 kg cow BW) were reduced in HVY cows. Scasta et al (2015) reported that large cows are not able to meet genetic production potential in a semiarid high-elevation rangeland production environment in Wyoming and, similar to the current research, smaller cows had greater weaning efficiency ratios than larger cows.…”
Section: Cow Bwsupporting
confidence: 78%
“…But other measures of productivity (pregnancy rates and net returns) were comparable with LGHT cow productivity, even though measures of weaning efficiency (kg of calf BW weaned per 100 kg cow BW) were reduced in HVY cows. Scasta et al (2015) reported that large cows are not able to meet genetic production potential in a semiarid high-elevation rangeland production environment in Wyoming and, similar to the current research, smaller cows had greater weaning efficiency ratios than larger cows.…”
Section: Cow Bwsupporting
confidence: 78%
“…The total pounds weaned ranges from 50,000 lb for 1,000 lb cows to 35,500 lb for 1,400 lb cows if larger cows offer no advantage in calf weaning weight (Table 1). Finally, the only cow size capable of weaning 50% of her body weight would be the smallest 1,000 lb cows; a result that is also supported by ranch level data in Scasta et al 16 (Table 1). Thus, because smaller cows require less forage, more individual cows can be placed on the same pasture and more total calf crop weight produced if the growth potential of larger cows is constrained by the environment.…”
Section: Contemporary Drought Mitigation Strategies Using Livestock Gsupporting
confidence: 67%
“…15 Contradictory results from a semi-arid rangeland environment in Wyoming recently indicated however that smaller cows weaned calves as heavy as the largest cows and may have an advantage over large cows due to their ability to reduce forage inputs while simultaneously increasing total output measured in annual total weaned weight of calves. 16 Using this general result for the cow size*rangeland environment interaction, we developed a hypothetical modeling scenario presented in Table 1 that we suggest for western rangelands. We used a formula assuming that forage dry matter intake (DMI) is 2.2% of a lactating cow's body weight on low quality forage 17 for five cow sizes (Table 1, Fig.…”
Section: Contemporary Drought Mitigation Strategies Using Livestock Gmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The provision of shade and water offers 17 y Assuming an average 500 lb weaned calf across all cow sizes and across the drought gradient. 16 Calculated as calf weight:cow weight with a common target of a cow weaning 50% of her body weight or an efficiency ratio of 0.5.…”
Section: Contemporary Drought Mitigation Strategies Using Livestock Gmentioning
confidence: 99%